THE ART OF ACHIEVING WHOLENESS: Adult-Learning in Presence and Listening Intercultural Encounter in Healthcare and Counselling before and during Covid-19 - Ulrike Elsdörfer (MAHABBAH: Journal of Religion and Education, 2021)
Counselling in healthcare is a method-based encounter between two persons. This is at least the definition according to psychology. One person, the client, has the chance to express mental, social and physical problems. The other person, the counsellor or therapist, makes use of her or his knowledge, intuition and responsiveness, in order to explore and heal. Spiritual counselling follows the same procedure. The counsellor is a trained religious person, aspects of spirituality give a distinct notion to the process. Group therapies relate to the needs of people in indigenous worlds, and non-western thinking as well as post-colonial analysis assists to make visible deep social shifts between different societies in a globalized world. Presence and listening are the two dominant qualities of a therapist, a counsellor or a spiritual advisor in this context. What happens, if exactly these qualities are rejected by needs of healthcare? How are the impacts of a globalized pandemic like COVID-19 on this concept of therapy, counselling and encounter in spiritual dimensions? What will lead to a form of community and social life? How does mental health prevention look like in times of challenges?